2013
DOI: 10.1038/aja.2013.34
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone deterioration at the greater trochanter of mice with unilateral obstructive nephropathy

Abstract: Our previous study showed the early molecular responses of bone in response to obstructive nephropathy in a unilateral ureteral obstruction (UUO) mouse model. Here, we addressed the changes in trabecular bone properties at greater trochanter, the proximal and the distal metaphysis of femur in UUO mice. The male mice were subjected to UUO (n510) or sham operation (n510). All mice were killed on day 7 after the surgical operation. The micro-computed tomography (micro-CT) analysis for different femoral trabecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Hand‐drawn contours were used to isolate the regions of interest for both cortical and trabecular compartments. Two volumes of interest (VOI) were established: a 1 mm VOI at the mid‐diaphysis of the femur for cortical bone, and a 50‐section VOI in the proximal metaphysis region for trabecular bone, as described elsewhere . Reconstructed 3D images were generated using CTvol (Skyscan Bruker MicroCT).…”
Section: Methodsmentioning
confidence: 99%
“…Hand‐drawn contours were used to isolate the regions of interest for both cortical and trabecular compartments. Two volumes of interest (VOI) were established: a 1 mm VOI at the mid‐diaphysis of the femur for cortical bone, and a 50‐section VOI in the proximal metaphysis region for trabecular bone, as described elsewhere . Reconstructed 3D images were generated using CTvol (Skyscan Bruker MicroCT).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we only evaluated heart tissue, but transcriptomic changes induced by UUO probably occur in other organs. Though UUO is a widely used model of tubulointerstitial kidney fibrosis, multiple studies have reported changes in lung function, bone metabolism and structure, and cognitive and neuropathological damage following obstructive nephropathy [ [57] , [58] , [59] ]. Hence, the global changes occurring after UUO cannot be underestimated but instead studied further to understand and treat better the systemic complications of renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study analyzing bone histopathology in a Sprague Dawley rat model that was given adenine for 4 weeks to induce CKD and a high-phosphorus diet for 38 weeks showed changes in trabeculation of loose and thin-walled bones, which characterizes osteoporosis (Ni et al, 2018). Another study using the ICR model of CKD mice induced by the UUO method for 7 days showed a decrease in trabecular bone mass in the trochanteric part of the mouse femur (Gu et al, 2013). The current study using male white rats of the Wistar strain (Rattus norvegicus) induced by the UUO method to produce a CKD model showed that the most distant gap between trabecular bone tissue, demonstrating the osteoporosis process, was on the 28th day after CKD modeling.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study analyzing bone histopathology in a Sprague Dawley rat model that was given adenine for 4 weeks to induce CKD and a high-phosphorus diet for 38 weeks showed changes in trabeculation by loose and thin-walled bones, which characterizes osteoporosis (Ni et al, 2018). Another study using the Institute of Cancer Research (ICR) model of CKD mice induced by the UUO method for 7 days showed a decrease in trabecular bone mass in the trochanteric part of the mice femur, indicating sensitivity to intervention using the UUO method (Gu et al, 2013). Data regarding the onset progression of bone pathological conditions in experimental animal models with CKD, particularly in Wistar rats induced by the UUO method, are still limited.…”
Section: Introductionmentioning
confidence: 99%